Complete knowledge in C - Dey, Sukhendu; Dutta, Debobrata (New Delhi: Narosa Publishing House, 2013)
Complete Knowledge in C presents a detailed exposition of C in a simple informative style and discusses various features of C language systematically. The book will be great use to the undergraduate and postgraduate students of engineering and computer applications as well as for the professionals.
Includes History of C and index
Keywords: C Programming -- Computer programming